The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/os.12494
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Treatment of Arterial Occlusion after Knee Arthroplasty: The Sooner, the Better

Abstract: Knee arthroplasty, including total knee arthroplasty (TKA) and unicondylar knee arthroplasty (UKA), is an effective procedure for patients with severe knee joint diseases. Arterial occlusion after knee arthroplasty is a rare but severe complication. However, there are few comprehensive reviews or analyses focusing on it. In this study, we presented a case of successful treatment of acute arterial occlusion of the popliteal artery after TKA by emergent balloon angioplasty, and conducted a review and analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 34 publications
(32 reference statements)
0
18
0
Order By: Relevance
“…Early diagnosis and treatment are essential for limb salvage [7]. A review of arterial injuries after TKA by Li et al [11] found pulselessness to be the most common presentation usually occurring within 24 h. We presented a unique case of delayed arterial thrombosis after primary TKA with initial complaints of neurologic dysfunction that required a TMA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Early diagnosis and treatment are essential for limb salvage [7]. A review of arterial injuries after TKA by Li et al [11] found pulselessness to be the most common presentation usually occurring within 24 h. We presented a unique case of delayed arterial thrombosis after primary TKA with initial complaints of neurologic dysfunction that required a TMA.…”
Section: Discussionmentioning
confidence: 99%
“…The most common presenting symptoms after arterial injury following TKA include pulselessness, poikilotherm, pain, paresthesia, pallor, poor capillary refill, paralysis, decreased ABI, mottling, swelling, blistering, and necrosis [11]. Motor weakness can also be a sign of vascular injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If a popliteal thrombus develops following TKA, prompt recognition and evacuation with surgery instead of conservative treatment is associated with better outcomes. [ 16 ]…”
Section: Discussionmentioning
confidence: 99%
“…Vascular complications are rarely seen in total knee arthroplasty (TKA), and injuries are classified as (i) iatrogenic vascular injury, (ii) artery occlusion, and (iii) pseudoaneurysm [1]. While there is a low risk of popliteal artery penetrating injuries, iatrogenic vascular injury is seen at the rate of 0.003% [2,3]. Although popliteal artery occlusion following TKA is seen more often than iatrogenic injuries, the rate has been shown to be 0.03%-0.2% [4,5] and the rate of chronic vascular insufficiency after TKA is estimated to be 2% [6].…”
Section: Introductionmentioning
confidence: 99%